Evaluation of Field Work Practice Programs with Using Logic Model - Juliwardi, Ilham; ., Sukardi; ., Krismadinata (Journal of Education Research and Evaluation, 2019)
This study aims to evaluate the Implementation of Field Work Practices of SMK Negeri 1 Padang. Evaluation of Field Work Practices is seen from the aspects of Input, Process, Output, Outcome faced in the implementation of street vendors. The research method used is a combination of Concurrent Embedded design methods, combining quantitative and qualitative research methods sequentially, where in the first stage the study uses quantitative methods and in the second stage qualitative methods. The results showed that the Implementation of Field Work Practices at SMK Negeri 1 Padang Electrical Engineering expertise program as a whole included. Input evaluation according to reality obtained an average standard score of 74.27% with the Fair category, and Input evaluation according to expectations obtained an average standard score of 89.58% with the Very Good category. Process Indicators according to reality obtained a percentage level of 74.14% with the category Fair. As for the Process indicator as expected, a percentage level of 88.56% was obtained with the Good category. Output indicators according to reality obtained a percentage level of 72.65% with the category Fair. As for the Output indicator as expected, a percentage level of 89.13% was obtained. with the category of Very Good. Outcome indicators according to reality obtained a percentage level of 72.36% with the category Fair. As for the Outcome indicator as expected, a percentage level of 88.41% was obtained with the Good category. Based on the findings of this study it was concluded that the Field Work Practices program for students in the SMK Negeri 1 PadangÂ  were still in the Fair category, which needed to be improved for each aspect.